Pola Aktivitas Fisik Mahasiswa di Era Digital - Muhammad Akbar Syafruddin; Muhammad Harliawan (Dharmas Journal of Sport, 2026)
This study used a quantitative approach with a descriptive approach, aiming to describe the physical activity patterns of students in supporting their studies in the digital era. The population in this study were all students of the Physical Education, Health, and Recreation Study Program at the Faculty of Public Health, Universitas Negeri Malang (FIKK UNM), while the sample size was 150 students selected using a purposive sampling technique. Data collection was conducted through interviews with several indicators, including physical activity patterns, frequency, duration, and type of physical activity. Based on the results, it can be concluded that the majority of students have a physical activity pattern that is quite good for supporting their studies, as indicated by the high percentage of students who regularly engage in physical activity, both in terms of frequency, duration, and type of activity. Most students engage in physical activity 2–3 times per week for 30–60 minutes and tend to choose light to moderate exercise that is easy and flexible to do between academic activities. Keywords: Physical Activity, Students, Digital Era